2008
DOI: 10.1148/radiol.2471070420
|View full text |Cite
|
Sign up to set email alerts
|

Iodixanol 320 Results in Better Renal Tolerance and Radiodensity than Do Gadolinium-based Contrast Media: Arteriography in Ischemic Porcine Kidneys

Abstract: Plasma iso-osmotic iodine-based contrast media used at commercially available concentrations have superior attenuation and nephrotoxic profiles compared with equal volumes of hyperosmotic nonionic 0.5-1.0 mol/L gadolinium-based contrast media when performing renal arteriographic procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…The 2 also showed significant radiopacity and the chemistry of {Re 6 Se 8 }-based compounds at present is studied well enough to create highly water soluble compounds with properties suitable for use as X-ray It is important to note, that to date the most utilized alternative to iodinated contrast media are gadolinium-based preparations (Gd (Z = 64)). However, Gd-based agents as radiocontrast media [20,21] are used very rarely, because these agents may cause severe adverse reactions, especially at high doses used for X-ray diagnostics (e.g., CT and conventional angiography) [22][23][24][25][26][27]. Furthermore, several research groups have shown that X-ray contrast of Gd-based agents is from four to eight times weaker than that of I-based ones taken with equal concentration of the heavy element [24,28,29].…”
Section: Ct-scan Experiments On Molybdenum and Rhenium Hexacyanide Clumentioning
confidence: 99%
“…The 2 also showed significant radiopacity and the chemistry of {Re 6 Se 8 }-based compounds at present is studied well enough to create highly water soluble compounds with properties suitable for use as X-ray It is important to note, that to date the most utilized alternative to iodinated contrast media are gadolinium-based preparations (Gd (Z = 64)). However, Gd-based agents as radiocontrast media [20,21] are used very rarely, because these agents may cause severe adverse reactions, especially at high doses used for X-ray diagnostics (e.g., CT and conventional angiography) [22][23][24][25][26][27]. Furthermore, several research groups have shown that X-ray contrast of Gd-based agents is from four to eight times weaker than that of I-based ones taken with equal concentration of the heavy element [24,28,29].…”
Section: Ct-scan Experiments On Molybdenum and Rhenium Hexacyanide Clumentioning
confidence: 99%
“…In animal models, the increase of fluid viscosity related to the use of dimeric contrast agents seems to enhance the resistance to urinary flow in renal tubules of rats and intrarenal interstitial pressure may significantly rise as well [29,30]. On the other side, in the study by Elmståhl et al, the selective injection of about 70 mL of iodixanol into the renal artery of pigs did not cause any apparent renal effects [31]. Additionally, no clinical data has shown an association between contrast media viscosity and risk for CIN in humans [32].…”
Section: Discussionmentioning
confidence: 92%
“…15 In fact, histological data from a few animal studies suggest that Gd-CM induces acute tubular necrosis and cytoplasmic vacuolization in renal tubular cells in several hours. [16][17][18] For the above reasons, we further used a less stringent criterion (a decrease >10% in GFR) for AKI. This may explain why we found a higher incidence of AKI after administration of Gd-CM at the doses for MRI and MRA examinations.…”
Section: Discussionmentioning
confidence: 99%